Enhancing assistant teachers' (PPM & PPM PPKI) psychological knowledge and skills in handling typically developed children in Sabak Bernam, Selangor - Janon, Nazariah Shar'ie; Abdul Khaiyom, Jamilah Hanum; Ayub, Ayunni; Dollah, Abu Hassan (Knowledge Transfer Centre, Universiti Sains Malaysia, 2018)
This paper aims to enhance assistant teachers' psychological knowledge and skills in handling . typically developed children. A pre-post study · design of 50 participants (i.e., PPM & PPM PPKJ) from 38 schools in Sabak Bernam Selangor was employed. The individual and joint effectiveness of the two modules (Module I and Module 2) were measured by a developed test. The test consists of items that are categorized under three domains which are knowledge, attitudes and practices. The test was given to participants before and after the workshops. Results show that a bigger improvement of scores was noted in post single assessment of Module 1 and Module 2 and post assessment of combined Module 1 and Module 2. The results indicate that the participants achieved greater scores on the knowledge and skills of children's development after attending the workshops of Module 1 and Module 2. Overall, these results imply that there is sufficient evidence to draw a conclusion about the effectiveness of the two modules in enhancing PPM & PPM PPKJ's psychological knowledge and skills in understanding and ·managing typically developed children.